2019
DOI: 10.21608/assjm.2019.42223
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Copper Oxide, Tri-calcium Phosphate and Silicon Dioxide Nanoparticles in Controlling Black Scurf Disease of Potato

Abstract: Black scurf disease caused by Rhizoctonia solani, was a serious and common disease on potato worldwide. Effect of nanoparticles forms of Tri-calcium phosphate, copper oxide and silicon dioxide nanoparticle was evaluated at five concentrations to control black scurf disease in vitro and in vivo. Examination of treated R. solani with different tested nanoparticle was done using Transmission Electron Microscope (TEM). Activities of defense related enzyme were determined in artificially inoculated potato plants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
6
5
0
Order By: Relevance
“…Numerous studies have reported the antimicrobial activity of Cu-NPs against several fungi [43][44][45][46]. The results of the present study indicate that all of the copper forms hyphal growth in a dose dependent manner, with Cu-NPs and CuO-NPs showing the most inhibiting effect against the pathogen.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Numerous studies have reported the antimicrobial activity of Cu-NPs against several fungi [43][44][45][46]. The results of the present study indicate that all of the copper forms hyphal growth in a dose dependent manner, with Cu-NPs and CuO-NPs showing the most inhibiting effect against the pathogen.…”
Section: Discussionsupporting
confidence: 49%
“…growth and conidia germination when treated with copper sulfate. Meanwhile, nanoforms of copper have been reported to exert biocidal effects on different classes of fungi [41][42][43][44][45][46]. However, there are only a couple of reports on the influence of Cu-NPs on C. gloeosp.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy was high at concentration 200 mg/L and decreased with decreasing the concentration. Similar results were given by El-Shewy et al (2019) who reported that CuONPs inhibited the growth of R. solani by 55.19 % at concentration 200 μl/L. The recent study of Oussou-Azo et al (2020) demonstrated that the mycelial growth of Colletotrichum gloeoesporioides was inhibited by 76.8% with Cu-NP at concentrations of 200 mg/ml.…”
Section: Discussionsupporting
confidence: 83%
“…Due to their unique smaller size, larger surface area and better stability, NPs can serve as a preferable chemical (pesticide) delivery system and may also enhance crop yield by nutrient and water management (Rai et al, 2018), suggesting that nanotechnology is being a promising application approach for sustainable agriculture. An array of publications has been demonstrated the antifungal toxicity of CuONPs towards Phytophthora infestans (Giannousi et al, 2013) Ismail, A.M. and phytopathogenic fungi, such as A. alternata and Botrytis cinerea (Ouda, 2014), A. alternata, Fusariun oxysporum, Curuvularia lunata and Phoma distructiva (Kanhed et al, 2014), tomato Fusarium wilt and Verticillium wilt (Elmer and White, 2016), R. solani (El-Shewy et al, 2019) and powdery mildew of rose (Hao et al, 2019), Furthermore, MgONPs have enormous potential as antifungal agent against fungal diseases caused by R. solani (El-Argawy et al, 2017), A. alternata, F. oxysporum, Rhizopus stolonifer, and Mucor plumbeus (Wani and Shah, 2012), F. oxysporum f. sp. lycopersici (Parizi et al, 2014) and P. nicotianae and Thielaviopsis basicola (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While, Cao et al [33] stated that CuNPs exhibited a powerful antifungal activity against Corticium salmonicolour when sprayed on pink disease infected rubber trees. Also, Ca 3 (PO 4 ) 2 and CuO NPs reduced infection percentage and disease severity of black scurf of potato tuber caused by R. solani [34].…”
Section: Discussionmentioning
confidence: 99%